In Type 2 Diabetes Patients Cardiovascular-Renal Disease is a Lifetime Risk Factor - Kashif Javed, Ali Asad Ullah, Iqra Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research is to establish whether or not cardiovascular-renal illness is a life-threatening condition in people with type-2 diabetes by using a case-control design. Study Design: Observational/Cohort study Place and Duration: Lahore general hospital/ Mayo Hospital Lahore.Jan 2020-Jun 2020 Methods: This research had a total of 170 individuals, both sexes. Patients ranging in age from 20 to 85 were included in this study. All the patients had type 2 diabetes. Individuals who participated provided detailed demographic information such as their age and gender as well as their body mass index (BMI), blood pressure, cholesterol, glucose, smoking, physical activity, food, and comorbiditie. Frequency of CVRD among all cases was measured. Myocardial Infarction (MI), heart failure (HF), stroke, chronic kidney disease (CKD), all-cause mortality, and cardiovascular (CV) death rates were evaluated. Complete data was analyzed using SPSS 22.0 version. Results: In current study males were 100 (58.8%) and 70 (41.2%) females in our study. Mean age of the patients was 56.8±8.98 years with mean BMI 30.5±6.34 kg/m2. Mean systolic and diastolic blood pressure of all the cases were 129.3±7.41 and 79.6±4.61 mmHg. Physical inactivity was mostly found among 90 (52.9%) cases and frequency of smokers was 65 (38.2%) cases. Hypertension, obesity and hyperlipidemia were the most common comorbidities. 105 (61.8%) cases had cardiovascular renal disease in which myocardial infarction 55 (52.4%), heart failure 67 (63.8%), stroke 52 (49.5), CKD 90 (85.7%) and mortality 35 (33.3%) was significantly higher than that of the diabetic patients without cardiovascular renal disease. Conclusion: In this research, we found that the cardiovascular renal disease among patients with type 2 diabetes found to be a lifetime risk resulted high number of myocardial infarction, heart failure, stroke and chronic kidney disease. There was high mortality rate among patients of diabetes 2 mellitus with CVRD.